BIODIVERSITY OF WILD PLANT SPECIES OF POLTAVA REGION AS SOURCES OF VALUABLE GENETIC MATERIAL FOR SELECTION - Bilyk, O. M.; Holovash, L. M.; Kocherga, V. Ya.; Kharchenko L. Yа.; Pospielova, G. D. (Scientific Progress & Innovations, 2021)
The biodiversity of wild plant species in Poltava region has been studied in the article. It has been determined that at present in Poltava region, as a center of agro-industrial development, changes are taking place in species composition and distribution of plants. Groups of agricultural vegetation and field weeds, ruderal vegetation, and artificial tree plantations became dominant. Taking into account these facts, the aim of the article was to identify places of growing and collect samples to preserve the genetic diversity of wild flora of Poltava region. The research methodology included examination of coenoses, seed collection of fodder medicinal, industrial, vegetable and ornamental crops during expeditions in mid-August. The locations of Red Data Book and regionally rare plants were registered separately. The studies began in 2016 as part of a search program – “Involvement in the National Gene Bank of plant forms of folk selection and wild related species of cultivated plants, adapted to the conditions of the Central Forest-Steppe of Ukraine” and are continuing now. During this period, 254 plant samples have been collected, and the total length of the route made 580 km. A complex of work was organized and carried out to perform the task of expedition surveying the territories of the natural reserve fund, natural-historical sacred places (mounds, etc.) and monuments of garden and park art in Poltava region. The study of the vegetation of historical monuments: mounds, squares and cemeteries indicates that preserved and scientifically valuable vegetation and flora are presented on a vast majority of these monuments in their natural state. While summarizing the collected data, it has been found that steppe vegetation has been preserved on the tops or protection embankment elevations of historical monuments, mainly those on which there are (or were) geodetic signs. The involved seed and planting material is characterized by the indicators of adaptability to environmental stress factors and resistance to biotic factors. Samples of wild fodder legumes and grasses, wild relatives of oil plants, wild relatives of industrial crops, etc. are valuable. The collected samples were transferred to the resource subdivisions of the institutions of STE “Plant Gene Fund” specializing in relevant crops, for in-depth studying economic and biological characteristics and properties, and further including the best of them in the National Gene Bank of Plants of Ukraine and using in breeding, scientific and other programs by institutions of Ukraine. The value of the material is explained by the fact that it is autochthonous Ukrainian, so it is adapted to the conditions of Ukraine. The results of the expedition indicate the expediency of further survey, covering other settlements of Ukraine and involving a wider diversity of species.